Collection and Evaluation of Wayanad Turmeric (Curcuma longa l.) for yield and quality - Anu T.S (Department of Plantation Crops and Spices, College of Horticulture, 2019)
Turmeric (Curcuma longa L.) is a rhizomatous perennial herb and an important sacred spice of India. It is used as a spice, colourant and an aromatic stimulant in several medicinal preparations. Wayanad local turmeric is reported to contain an average of 9.4 per cent curcumin. Due to the advent of improved varieties, the traditional cultivars of Wayanad are eroding. Keeping in view of this fact the study was undertaken to evaluate the local Wayanad accessions for yield and quality.